Social Mobility through Migration to the Colonies: The Case of Algeria - van Leeuwen, Marco H. D.; Maas, Ineke (The Journal of interdisciplinary history, 2022)
Most migrants move to further their economic and social position. How successful were they, and which migrants succeeded best? Would they have fared better if they had stayed at home? These questions are often raised regarding recent migrants to the United States and Europe, who often entered the labor market in relatively low positions. During their lifetime, many migrants improve their social position, as do subsequent generations. The migrants to Algeria during French colonial rule, however, entered the labor market at the higher echelons of society. Did they fare better than their parents? If so, did their descendants keep their relatively privileged colonial position? The effects of gaining or losing social, cultural, economic, and human capital appear to be different for various groups of migrants who moved to colonies, tweaking existing theories in economic history, settler history, and the sociology of migration.